Pengetahuan dan Kinerja Siswa SMA Negeri 1 Jorong, Kabupaten Tanah Laut dalam Budidaya Jamur Tiram (Pleorotus ostreatus) - Kariyati Kariyati; Mochamad Arief Soendjoto; Sri Amintarti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Modul on Oyster Mushroom cultivation was used in training for 17 students ofGrade X and XI, SMA Negeri 1 Jorong, Tanah Laut District, South Kalimantan Province. The purpose of the research was to measure their knowledge as well as performance and appoint students as cadres of oyster mushroom cultivation. Knowledge of the students was tested pre-training and post-training. Their performances were evaluated through 6 parameters. Those were discussion, making the planting medium, making leaflet, making school magazine, behaving as a guide, and making processed food based on Oyster Mushroom. The knowledge of the students increased post-training, although varied. In general their performanceswere very satisfying. Of 17 students, 15 wereappointed as cadres on Oyster Mushroom cultivation.Keywords:        cultivation, knowledge, Oyster Mushroom, performance, student